2008
DOI: 10.1016/j.joen.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Homeostatic Mechanism of Dental Pulp with Age: Expression of the Core-binding Factor Alpha-1, Dentin Sialoprotein, Vascular Endothelial Growth Factor, and Heat Shock Protein 27 Messenger RNAs

Abstract: Aim: Dental pulp has various characteristics in the pulp chamber, but only a few biological evaluations about the effect of age on dental pulp tissue have been reported. The purpose of this study was to compare dental pulp from young and from adult rats to characterize the homeostatic mechanism.Methodology: Dental pulp cells (DPCs) were obtained from the first molar of rats, weighing 150 g each for the young group and 350 g each for the adult group. Expression of Cbfa-1, VEGF or HSP27 mRNAs by cultured pulp ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Consistent with the results showing enhanced Nrf2 translocation in response to heat exposure, the expression levels of SOD, HO-1, GST, GR, and GCL were increased. These results are consistent with the results of another study showing that the self-defense system in adult dental pulp cells involves the expression of self-defense proteins (39).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the results showing enhanced Nrf2 translocation in response to heat exposure, the expression levels of SOD, HO-1, GST, GR, and GCL were increased. These results are consistent with the results of another study showing that the self-defense system in adult dental pulp cells involves the expression of self-defense proteins (39).…”
Section: Discussionsupporting
confidence: 93%
“…NAC is a cysteine derivative that is more stable than glutathione and protects cells against oxidative stress in various ways (39). In our study, the addition of NAC to cells blocked heat-induced IL-8 and Nrf2 target gene expression (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…As mentioned above already, VEGF has been shown to play an important role in bone formation besides its angiogenic activity. Indeed, it has been shown that VEGF is upregulated at the sites of bone formation [72] and is involved in bone healing [73]. These data indicate that VEGF -as an inflammatory mediator -plays a functional role in bone formation and thereby calcification.…”
Section: Angiogenesis Growth Factors and Non-rheumatic Aortic Stenosismentioning
confidence: 98%
“…Further, Tate et al [16] and Suzuki et al [17] verified the expression of HSP in dental pulp cells after experimental cavity preparation by laser ablation. Moreover, Matsuzaki et al [18] reported an increased in mRNA levels of HSP27 in the pulp. However, the expression of HSP27 in dental pulp cells after teeth separation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%